Health Insurance Literacy among the Insured person of the Health Insurance Organization in Tehran, Iran - Parvaneh Bagheri; Alireza Abadi; Ehsan Zarei (Payesh)
Objective(s): Health insurance literacy (HIL) is the knowledge, ability, and confidence of people to find and evaluate information about insurance plans, choose the best plan and how to use it. This study was conducted to examine the level of HIL among the insured person of the Iran Health Insurance Organization in Tehran. Methods: This cross-sectional study was conducted in 2023 with the participation of 309 insured person. The data were collected using a 27-item questionnaire that included three dimensions of access, insurance terms, and performance skills. The validity and reliability of the questionnaire were confirmed. Data analysis was performed in SPSS.24 using T-test and One-way ANOVA. Results: The mean score for access was 8.5±1.91, insurance terms 10.21±2.46 and performance skill was 22.94±3.23. The overall mean HIL score was 41.64±6.22. The HIL status of 60% of the insured person was intermediate and 40% was low. The mean score of HIL was higher among people living in the northern region, those covered by the special diseases fund, those with a monthly less income, and those without supplementary insurance. The HIL level was also higher among people whose source of insurance information was friends and acquaintances (P<0.05). Conclusion: The majority of people had relatively low levels of HIL. Knowing the level of HIL and the factors that influence it can guide policy makers in developing educational interventions to remove barriers and improve HIL. Educational interventions through public media such as television, short videos on the websites and applications of insurance organizations and social media, and the provision of insurance information on waiting room monitors in medical centers are suggested to improve HIL.